Feedback between Basin Morphology and Sediment Transport at Tidal Inlets: Implications for Channel Shoaling - Douglas R. Krafft; Richard Styles; Mitchell E. Brown (Journal of Marine Science and Engineering, 2022)
Increasing societal pressures (e.g., population growth and urbanization) are driving land use change practices in coastal areas that could potentially alter the hydrodynamics and sediment transport patterns near coastal inlets in ways that might exacerbate existing shoaling conditions. To investigate the potential impact of coastal development, a numerical model is used to predict the long-term evolution of an idealized lagoonal-type barrier island inlet under five different morphological conditions that transitioned from net sediment import to net sediment export. The simulations were designed to address the potential effect of inter-tidal placement and land reclamation on sediment transport and the resulting deposition/erosion patterns. Estuaries that were deeper and devoid of extensive tidal flats tended to promote sediment import and had a greater propensity to exacerbate channel shoaling. Simulations that were characteristic of inter-tidal placement showed net export, yet the likelihood of channel shoaling was increased because some of the material eroded from the tidal flats was deposited in the deeper channels as opposed to being carried out the inlet throat. Alternatively, it was found that regions in which the intertidal area was restricted to elevations higher in the tidal frame, which also showed a net export, produced greater sediment loss in the inter-tidal zone that tended to bypass the deeper sections, reducing the likelihood of channel shoaling.